Relationship between Level of Knowledge and Medication Adherence among Hypertensive Patients - Fetty Yublika Pasole; Yosin Herloheti Pella; Serly Sani Mahoklory (CV. Global Health Science Group, 2026)
The high number of hypertension cases in the East Nusa Tenggara region, namely 76,130 people, and in the Kupang region, namely 63.32% of cases, shows that this problem is still a serious concern. The data alsoshows that 13.3% of people with hypertension do not take their medication regularly.This condition is caused by various factors, such as patient noncompliancewith doctors' recommendations to take medication every day, delays intaking medication, boredom with long-term treatment, lowawareness of the risks of hypertension, and lack of knowledge aboutthe importance of drug therapy. This study aims to analyze the relationship between knowledge level and medication adherence among hypertensive patients at the Tarus Health Center in Kupang District. This is a quantitative study using an analytical observational design with a cross-sectional approach. Sample: The study included 100 respondents selected using purposive sampling. The measurement tool used was a questionnaire on hypertension knowledge and medication adherence. Data analysis was performed using the Spearman's Rank test. The study results showed a significant association between knowledge level and medication adherence in hypertensive patients with a p-value of 0.000 (p < 0.05). There is an association between knowledge level and medication adherence in hypertensive patients.